Spectra of the extended neighborhood corona and extended corona of two graphs - Chandrashekar Adiga; Rakshith B.R.; Subba Krishna K.N. (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2016)
In this paper we define extended corona and extended neighborhoodcorona of two graphs G_1 and G_2, which are denoted byG_1G_2 and G_1* G_2 respectively. Wecompute their adjacency spectrum, Laplacian spectrum and signlessLaplacian spectrum. As applications, we give methods to constructinfinite families of integral graphs, Laplacian integral graphsand expander graphs from known ones.